Placenta-specific 9, a putative secretory protein, induces G2/M arrest and inhibits the proliferation of human embryonic hepatic cells. Issue 6 (7th November 2018) - Ouyang, Cong; Pu, Yi-Zhi; Qin, Xu-Hui; Shen, Jinhua; Liu, Qing-Hua; Ma, Liqun; Xue, Lu
Abstract : Background: Placenta-specific 9 ( Plac9 ) is a putative secreted protein that was first discovered in the context of embryogenesis. The expression pattern of Plac9 during embryogenesis, together with the results of recent reports, suggest that Plac9 may play a role in the liver development. The present study was conducted to investigate the secretory characteristics of Plac9 and its potential role in liver cell physiology.Methods: Immunofluorescence was employed to identify the subcellular distribution of Plac9 . Cellular proliferative activity was analyzed by MTT assay and cell colony formation. The cell cycle distribution of Plac9 was analyzed by flow cytometry, and a functional analysis was performed using L02 cells following their stable infection with a lentivirus over-expressing Plac9 .Results: Plac9 is a novel protein that is localized to the cytoplasm and may be secreted through the classic endoplasmic reticulum-Golgi route. The overexpression of Plac9 inhibits cell growth and induces G2/M phase arrest.Conclusion: Our findings reveal a novel role for Plac9 in regulating cell growth.